Polish theatre revisited: theatre fans in the nineteenth century - Łuksza, Agata (Studies in theatre history and culture, 2023)
"Polish Theatre Revisited explores nineteenth-century Polish theatre through the lens of theatre audiences. Łuksza places special emphasis on the most engaged spectators, known as "theatremaniacs"-from what they wore, to what they bought, to what they ate. Her source material is elusive ephemera from fans' lives, such as notes scribbled on a weekly list of shows in the Warsaw theatres, collections of theatre postcards, and recipes for sweets named after famous actors. The fannish behavior of "theatremaniacs" was usually deemed excessive or in poor taste by people in positions of power, as it clashed with the ongoing embourgeoisement of the theatre and the disciplining of audiences. It was increasingly associated with "lowbrow" cultural fields, such as sports. Nevertheless, the theatre was one of the key areas where early fan cultures emerged, and "theatremaniacs" indulged in diverse fan practices in opposition to the forces reforming the theatre and its spectatorship. Polish Theatre Revisited brings back to life the passionate audiences of Polish playhouses in the nineteenth century, and presents a history in which fans come out of the shadows"--